Successful laparoscopic treatment of a ruptured primary ovarian pregnancy - (:unkn) unknown (JOURNAL AMER ASSOC GYNECOLOGIC LAPAROSCOPISTS, 2002)
A 26-year-old woman had classic symptoms of primary ovarian pregnancy. Ultrasound examination disclosed a cystic mass surrounded by a complex mass that was compatible with hematoma in the pouch of Douglas, as well as an intrauterine device (IUD) displaced near the isthmic portion of the uterine cavity. Laparoscopy revealed a ruptured gestational sac in the cul-de-sac that was encapsulated by a hematoma originating from the right ovary. All deep-seated products of conception were excised from the ovary, and the IUD was removed. Treatment was successful and avoided more invasive intervention.